Definition, Context and Digital Tools for the Development of Data Journalism in Spain - Lopez Lopez, Pilar Jose; Martínez, Fátima (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2014)
Internet proves to be a large database of millions of journalists, the question is whether we have enough tools to process, compare and analyze them properly in order to make them intelligible to those accustomed to the new electronic reading device. We are in a field where research and tools are yet to be discovered and even to develop. The current trend seems to combine increasingly, journalism with new computer skills related to digital skills in statistics and data. At this point, the current relevance acquires data called journalism. This paper aims to make an approach to the concept and devel-opment of Journalism Data (big data) in the new digital ecosystem generated in Spain. Therefore be provided with a defini-tion of the meaning of this new denomination, as well as indicating some of the new digital tools that can help any journalist when facing a multimedia news submit required data, charts and statistics Fashion simple and attractive as possible to readers of the 21st century.